Basophil activation test positivity decreases with time in immediate allergic reactions to proton pump inhibitors - Fernández-Santamaría, Rubén; Salas, Maria; Ariza Veguillas, Adriana; Jiménez, María A.; González-Mendiola, María R.; Sánchez, María L.; Boteanu, Cosmin; Mayorga Mayorga, Cristobalina; Fernández-Duarte, Tahía Diana; Torres, María José; Laguna, José J. (Wiley, 2024)
Omeprazole is a widely prescribed proton pump inhibitor [1], with 1%–3% of adverse reactions being reported. Up to 86% of these reactions are IgE mediated [2] and half of them anaphylaxis [1]. An accurate diagnosis is essential, with skin testing (STs) showing high specificity and positive predictive value (PPV) (100%), but lower sensitivity (60%) and negative predictive value (NPV) (70%–90%) [2]. As stated in a recent position paper of the European Academy of Allergy and Clinical Immunology (EAACI), the basophil activation test (BAT) is a reliable option in the diagnosis of immediate hypersensitivity to proton pump inhibitors [3]. In fact, previous research from our group reported that BAT has a higher sensitivity than STs (73.8%) and similar specificity, PPV (100%) and NPV (66.7%) [1]. Interestingly, the combination of STs and BAT can increase sensitivity up to 85.7%, being BAT positive in 57.1% of patients with negative STs [1].
Keywords: Anafilaxia; Basophil activation; Allergy